TRAINING OF ACCOUNTANTS IN ESTONIA AND UKRAINE: COMPARISON OF EDUCATIONAL AND PROFESSIONAL PROGRAMS - Ozeran , Alla (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The article examines educational and professional training programs for specialists of the first (bachelor) level in the field of «Accounting» of Tallinn University of Technology and Kyiv National University of Economics named after Vadym Hetman. Based on the comparison of the programs, conclusions were made regarding the improvement of the training of accountants in Ukraine.